A NEW MODEL OF RURAL DEVELOPMENT BASED ON HUMAN CAPITAL AND ENTREPRENEURSHIP - Radosavljević, Darko; Josipović, Sonja; Kokeza, Gordana; Urošević, Snežana (Economics of Agriculture, 2022)
Rural development is one of the most important elements of the overall economic development. The level of entrepreneurship development, which is closely related to the available human capital of a certain area, has a particularly great impact on the speed and structure of the rural economic growth, along with outdoor amenities of rural areas. The paper provides an overview of foreign and domestic academic literature which deals with the issue of rural development and indicates the necessity and importance of achieving a stronger connection between rural outdoor amenities and the socio-economic development of rural areas. The paper also presents the results of the research aimed at the formulation of the relevant models of economic growth of rural areas in the 21st century. The aim of this paper is to point out the importance and possibility of implementing successful models of rural economic growth in Serbia.